Clinical outcomes of patients with acute coronary syndrome and moderate or severe chronic anaemia undergoing coronary angiography or intervention. Issue 7 (October 2018) - Ohana-Sarna-Cahan, Lea; Atar, Shaul
Background: There are limited data on the impact of chronic moderate or severe anaemia on the clinical outcomes of patients with acute coronary syndrome undergoing coronary angiography or percutaneous coronary intervention. Methods: We retrospectively compared two groups of consecutive patients with acute coronary syndrome according to their haemoglobin level on admission. The research group ( n =89) had a haemoglobin level of 10.9 g/dl or less and a control group ( n =79) of age-matched patients had a haemoglobin level greater than 10.9 g/dl. We studied drug therapy before, during and after intervention, and performed 1-year follow-up of bleeding complications according to the Bleeding Academic Research Consortium criteria, all-cause mortality and re-infarction, as well as haemoglobin level on discharge, 6 and 12 months after admission. Results: Compared to controls, a haemoglobin level less than 10.9 gon admission is associated with a higher rate of major bleeding: 26 patients (32%) versus none in the control group ( P <0.001); and the use of packed red blood cell (RBC) transfusion: nine patients (11.7%) versus none in the control group ( P =0.003) within the first 6 months post-catheterisation. However, the re-infarction rate and mortality were similar in the study and control groups: 9.2% versus 9.7% ( P =0.915) and 12.6% versus 8.9% ( P =0.434), accordingly. Conclusions: Chronic moderate or severe anaemia in patients with acute coronary syndrome undergoing coronary angiography or percutaneous coronary intervention is associated with a substantially increased risk of bleeding in the first 6 months. However, rates of mortality and re-infarction were similar.